A Campus Building Energy Consumption Monitoring System Based on B/S Architecture - Tang, Haifeng; Ju, Xiaoyu (Journal of Research in Science and Engineering, 2026)
The system architecture adopts the B/S (Browser/Server) structure. The client side does not require installation of any specialized software; a web browser is sufficient to access and use the monitoring system, enabling energy consumption monitoring anytime and anywhere. It offers good scalability, as future functional expansions and upgrades to the software only need to be implemented on the server side. Anyone can browse and use this system, making energy-saving promotion more extensive and effective.